High-gain UWB elliptical and circular slotted antipodal Vivaldi antenna for through wall detection - Ahmed, Sajjad; Katiran, Norshidah; Joret, Ariffuddin; Mohd Shah, Shaharil; Ahmed, Arslan; Tusin, Najwanisa (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The paper describes a high-gain ultra-wideband (UWB) elliptical and circular slotted antipodal Vivaldi antenna (ECS-AVA) that is designed for through-wall detection systems. The antenna flares are loaded with elliptical and circular slots to improve the gain and broaden the bandwidth. To validate the efficacy of the designed antenna, a prototype of ECS-AVA is fabricated and subjected to measurements. The experimental findings suggest that the designed antenna can handle signals effectively across a range from 3.1 GHz to 10.6 GHz, as shown by its measured impedance bandwidth, with │S11│≤ -10 dB. The obtained measurements results are consistent with the results of the CST simulation. The proposed antenna exhibits improved radiation patterns in the UWB band with peak gain values ranging from 4.8 dB to 11.9 dB.